Influence of Soil Water Status on Arbuscular Mycorrhizas in Three Perennial Grasses in Central Argentina - Busso, Carlos Alberto; Bolletta, Andrea Ivana; Flemmer, Andrea Cecilia; Montani, Tomás (Finnish Zoological and Botanical Publishing Board, 2022)
In this field study, we determined the effects of water stress, rainfed or irrigated conditions on the arbuscular mycorrhizal fungal (AMF) root colonization in the late-seral Stipa clarazii, the earlier-seral S. tenuis and the early-seral S. gynerioides at different developmental stages and sampling dates. We had two goals: (1) to document the levels of AMF root colonization, and (2) to examine the plant stress responses during imposed water stress in the three Stipa species. We tested the hypothesis that the effects of water stress on Stipa grasslands depend upon the interactions between plant AMF status and plant species. No consistent patterns in AMF root colonization frequency were observed relative to soil water levels. This suggests that AMF root colonization is highly plastic and responds to environmental factors that we do not yet understand. Mycorrhiza colonization was greater in the late-seral than in the earlier-seral species. Higher AMF root colonization levels in S. clarazii may partly explain its higher competitive ability in comparison with the earlier-seral species.